Changes of the morphological characteristics in a professional ice hockey player with regard to the eight week intensive fitness training: case study - Sigmund Martin; Tomáš Brychta; Iva Dostálová (Palacký University Olomouc, 2013)
The present study deals with monitoring the changes of the morphological characteristics in a professional hockey player (NHL) aged 22.5 years with regard to the eight weeks intensive fitness training. Fitness training occurred oﬀ the ice surface. To determine the body composition, the method of BIA and anthropometric procedure is used (Matiegka, Pařízková). Measurements were carried out in accordance with the recommended national and international standards. An eﬀect size of the diﬀerences in the selected individual values measured at diﬀerent times was assessed using 95% of confidence interval. Significant changes occur primarily at the level of body composition. Overall, the increase in fat free mass was 4 kg to the weight 79.3 kg (BIA). Representation of muscle increased from 51.4% to 54.5% (Matiegka). In absolute terms it is the increase in muscle from 47.1 kg to 49.9 kg. Body fat percentage decreased from 12.9% to 9.7% (Matiegka). This represents a reduction of 2.9 kg. There is no change at the level of skeletal and residual fractions. With regard to the eight week fitness training the major morhpohogical changes (80-90%) are experienced during the first half of the training (4 weeks). The survey results are of immediate use in the professional practice of the monitored player. It allows specific modifications to the training of the monitored player as well as other cooperating individuals in the chosen specialization.